Օտար տիրապետությունը Արարատյան երկրում (ԺԵ դ.) - Հ. Դ. Փափազյան (ՀՍՍՌ ԳԱ հրատ․)
Мелкие армянские княжества, которые при Захаридах господствовали в центральных районах Араратской области исторической Армении, смогли сохранить свое существование до середины XV в. Armenian small principalities that ruled during the period of Zacharides over the central districts of historical Armenia in Araratian region,succeeded to preserve their existence up-to the middle of XV c.
Keywords: Պատմություն